An Analytical Analysis of a Fiber-Optic Reflective Sensor - Kleiza, V.; Verkelis, J. (Elektronika ir Elektrotechnika, 2005)
The aim of this paper was to investigate the influence of the distance between the tips of the fiber-optic system and the light reflection body-mirror, the distance between the central point of the tip of light emitting and the point of the two light receiving fibers by modeling. This would enable us to obtain knowledge on the behavior of the whole system in a wide interval of the distance fiber tips mirror and to design displacement sensors of maximal sensitivity. With a view to obtain a high sensitivity and linearity the measurements, however must be performed in a narrow interval of displacement (±100μm) or even (±10μm). Light transmission in the reflection fiber-optic system was investigated by modeling for application as sensors. The sensitivity of the system to linear displacement was studied as a function of the distance between the tips of the light emitting fiber and the center of the pair reflected light collecting fibers by mirror positioning in wild interval. Sensitivity of the sensors will be maximal as distance b will be minimal approximately no bigger 3a cosθ . Modeling results shoved that sensitivity Ssub increase 20 times as b decrease from 4 mm to 1 mm. Ill. 5, bibl. 3 (in English; summaries in Lithuanian, English and Russian).